Association between sleep duration and depression in menopausal women: a population-based study - Zhang, Feng; Cheng, Long (Frontiers in Endocrinology, 2024)
Abstract Aims: This research investigated menopausal women older than 50 years to find whether there were any independent relationships between the duration of sleep they got and their prevalence of depression. Methods: National Health and Nutrition Examination Survey (NHANES) datasets from 2011-2020 were utilized in a cross-sectional study. Using multivariate linear regression models, the linear relationship between sleep duration and depression in menopausal women was investigated. Fitted smoothing curves and thresholds impact evaluation were used to investigate the nonlinear relationship. Then, subgroup analyses were performed according to smoking, drinking alcohol, diabetes, hypertension, heart disease, and moderate activities. Results: This population-based study included a total of 3,897 menopausal women (mean age 65.47±9.06 years) aged≥50 years; 3,159 had a depression score <10, and 738 had a depression score≥10. After controlling for all covariates, the prevalence of depression was 17% higher among participants with short sleep duration [OR=1.17, 95%CI=(0.65, 1.70), P＜0.0001] and 86% [OR=1.86, 95%CI=(1.05, 2.66), P＜0.0001] compared to participants with normal sleep duration. In subgroup analyses stratified by smoking and diabetes, the sleep duration and depression scores of non-smokers [β=-0.18, 95%CI= (-0.33, -0.02), P=0.0241] and diabetics were independently negatively correlated [β=-0.32, 95%CI= (-0.63, -0.01), P=0.0416]. Using a two-segment linear regression model, we discovered a U-shaped relationship between sleep duration and depression scores with an inflection point of 7.5 hours. Less than 7.5 hours of sleep was associated with an increased risk of developing depression [β=-0.81, 95%CI= (-1.05, -0.57), P＜0.001]. However, sleeping more than 7.5 hours per night increased the risk of depression considerably [β=0.80, 95%CI= (0.51, 1.08), P＜0.001]. Conclusions: Depression is associated with sleep duration in menopausal women. Insufficient or excessive sleep may increase the risk of depression in menopausal women. Keywords: Patient health questionnaire-9，Sleep duration，Menopausal women